2006
DOI: 10.1111/j.1447-073x.2006.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal spermatogenesis in mice unable to synthesize ascorbic acid

Abstract: Although exposure to environmental toxicants, including endocrine-disrupting chemicals, is thought to be a possible cause of male infertility, the pathogenesis of male reproductive disorders remains unclear. In the present study, we used Gulo-/- mutant mice, which are unable to synthesize ascorbic acid, to study the importance of dietary vitamin C (VC) on spermatogenesis. Regular chow containing approximately 110 mg/kg VC is unable to support the growth of these mutant mice, but a VC supplement in their drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…This testicular atrophy and arrest of spermatogenesis could also be related to impaired ascorbic acid uptake as a result of low extracellular sodium concentrations. Consistent with this potential mechanism, a similar impairment of spermatogenesis has been reported in mice unable to synthesize ascorbic acid (Yazama et al 2006). Other factors may also be involved.…”
Section: Discussionsupporting
confidence: 74%
“…This testicular atrophy and arrest of spermatogenesis could also be related to impaired ascorbic acid uptake as a result of low extracellular sodium concentrations. Consistent with this potential mechanism, a similar impairment of spermatogenesis has been reported in mice unable to synthesize ascorbic acid (Yazama et al 2006). Other factors may also be involved.…”
Section: Discussionsupporting
confidence: 74%
“…Sperm counts in healthy men around the world have fallen by about 50 per cent in the last 50 years in the Western world (Auger et al, 1995;Kasahara et al, 2002). This may be attributed to the insufficient spermatozoa (oligozoospermia) or the lack of spermatozoa (azoospermia) (Yazama et al, 2006). Carlsen et al, (1992) reported in declining sperm concentrations in normal men .…”
Section: Infertility Oxidative Stress and Vitamin Cmentioning
confidence: 99%
“…A unique pattern of HSP70 expression is associated with mouse spermatogenesis. Spermatocyte-specific HSP70, called HSP70-2, is expressed in pachytene spermatocytes during the meiotic phase [ 20 , 21 , 22 , 23 , 24 , 25 ]. The amino acid sequences of HSP70-2 are highly similar to those of heat-inducible HSP70s.…”
Section: Discussionmentioning
confidence: 99%